Ex 12.1

Ex 12.1, 1

Ex 12.1, 2

Ex 12.1, 3

Ex 12.1, 4 Important

Ex 12.1, 5

Ex 12.1, 6 Important

Ex 12.1, 7

Ex 12.1, 8 Important

Ex 12.1, 9

Ex 12.1,10 Important You are here

Ex 12.1, 11

Ex 12.1, 12

Ex 12.1, 13

Ex 12.1, 14 Important

Ex 12.1, 15 Important

Ex 12.1, 16

Ex 12.1, 17 Important

Ex 12.1, 18

Ex 12.1, 19 Important

Ex 12.1, 20

Ex 12.1, 21 Important

Ex 12.1, 22 Important

Ex 12.1, 23

Ex 12.1, 24

Ex 12.1, 25 Important

Ex 12.1, 26

Ex 12.1, 27

Ex 12.1, 28 Important

Ex 12.1, 29

Ex 12.1, 30 Important

Ex 12.1, 31

Ex 12.1, 32 Important

Last updated at May 7, 2024 by Teachoo

Ex 12.1, 10 Evaluate the Given limit: limβ¬(zβ1) (π§^(1/3) β 1)/(π§^(1/6) β 1) limβ¬(zβ1) (π§^(1/3) β 1)/(π§^(1/6) β 1) = (γ(1)γ^(1/3) β 1)/(γ(1)γ^(1/6) β 1) = (1 β 1)/(1 β 1) = 0/0 Since it is form 0/0, We can solve it by using (πππ)β¬(π₯βπ) (π₯^π β π^π)/(π₯ β π) = nan β 1 Hence, limβ¬(zβ1) (π§^(1/3) β 1)/(π§^(1/6) β 1) = limβ¬(zβ1) π§^(1/3) β 1 Γ· limβ¬(zβ1) π§^(1/6) β 1 = limβ¬(zβ1) π§^(1/3) β γ(1)γ^(1/3) Γ· limβ¬(zβ1) π§^(1/6) β γ(1)γ^(1/6) Multiplying and dividing by z β 1 = limβ¬(zβ1) (π§^(1/3) β γ(1)γ^(1/3))/(π§ β 1) Γ· limβ¬(zβ1) (π§^(1/6) βγ (1)γ^(1/6))/(π§ β 1) Using (πππ)β¬(π₯βπ) ( π₯^π β π^π)/(π₯ β π) = nan β 1 limβ¬(zβ1) (π§^(1/3) β γ(1)γ^(1/3))/(π§ β1) = 1/3 γ(1)γ^(1/3 β 1) = 1/3 Γ 1 = 1/3 limβ¬(zβ1) (π§^(1/6) β γ(1)γ^(1/6))/(π§ β1) = 1/6 γ(1)γ^(1/6 β 1) = 1/6 Γ 1 = 1/6 Hence our equation becomes = limβ¬(zβ1) (π§^(1/3) β γ(1)γ^(1/3))/(π§ β 1) Γ· limβ¬(zβ1) (π§^(1/6) β 6)/(π§ β 1) = 1/3 Γ·1/6 = 1/3 Γ 6/1 = 2